Colchicine induced polyploidy in coriander (Coriandrum sativum L.) - Purbiya, Rakesh; Verma, Rakesh Chandra; Dass, Preeti; Chouhan, Chhatar Sing (Current Botany, 2021)
The aim of this study was to find a suitable treatment combination that would effectively induce polyploidy in Coriander. In this study, colchicine concentrations and treatment durations were examined for improving the induction of polyploidy. The combinations of three colchicine concentrations such as 0.1%, 0.2% and 0.3% for 3 hrs per day for two to three days were tested in coriander. Three tetraploids were obtained in 0.2% colchicine treated population. The treatment of colchicine (cotton swab method) seedling with 0.2% for 3 days was suitable for induction of chromosome doubling. The control plant showed eleven bivalents (2n=2x=22) and polyploid plant showed twenty two bivalents (2n=4x=44) at diakinesis/metaphase-I in most of the PMCs. Anaphase-I distribution of chromosomes was normal (11:11) in control and in tetraploids distribution of chromosomes was (22:22) at each poles. In contrast with the normal plants, those treated by colchicine treatment often showed changes in height and width, in thickness of branches, in size, shape, texture of leaves, flowers, size of fruits and seed setting.